Distribution of chlorophyll and phytoplankton in Xiapu, Fujian. Issue 3 (February 2020) - Hao, Zhe; Feng, Ziyue; Zou, Xinqing; Feng, Weihua; Xu, Hengtao
Abstract: Phytoplankton is the primary productivity of the ocean, increasing their biomass through accumulating organic matter synthesized by photosynthesis. Chlorophyll a and pheophytin will all bring important influence on the recognition of biological optical information for phytoplankton. So it's necessary to analyse distribution of chlorophyll and phytoplankton. In this study, the concentration distributions of chlorophyll a and pheophytin in Xiapu were obtained. As a result, the overall trend of concentrations showed summer > spring> autumn > winter . This was mainly because of the difference of seawater temperature. The distribution of chlorophyll and phytoplankton varied with time. And they share a similar trend, indicating that chlorophyll content directly affects phytoplankton content.